Development in students of requirement for intercultural interaction - V I Kazarenkov; T B Kazarenkova (Peoples' Friendship University of Russia (RUDN University), 2010)
The role of development of requirement of the person in intercultural interaction in productive adaptation of students in multinational high school is considered.